The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1155/2023/4899372
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Genomic Sequencing of TSC1 and TSC2 Reveals Causal Variants in Individuals for Whom Previous Genetic Testing for Tuberous Sclerosis Complex Was Normal

Abstract: Tuberous sclerosis complex (TSC) is caused by inactivating variants in TSC1 and TSC2. Somatic mosaicism, as well as the size and complexity of the TSC1 and TSC2 loci, makes variant identification challenging. Indeed, in some individuals with a clinical diagnosis of TSC, diagnostic testing fails to identify an inactivating variant. To improve TSC1 and TSC2 variant detection, we screened the TSC1 and TSC2 genomic regions using targeted HaloPlex custom capture and next-generation sequencing (NGS) in genomic DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Newer tools, such as SpliceAI, are proving to be more sensitive for detecting deep intronic variants [ 73 ]. Many recent studies have also shown the utility in re-phenotyping and re-genotyping cases with NMI, where deep intronic variants have improved the diagnostic yield, including a recent study on TSC1/TSC2 [ 74 , 75 , 76 ]. Most deep intronic variants will require functional studies for their pathogenicity to be evaluated as per guidelines from the American College of Medical Genetics and Genomics (ACMG) and Association for Molecular Pathology (AMP) [ 71 , 77 , 78 ].…”
Section: Overview Of Genetics Of Tscmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer tools, such as SpliceAI, are proving to be more sensitive for detecting deep intronic variants [ 73 ]. Many recent studies have also shown the utility in re-phenotyping and re-genotyping cases with NMI, where deep intronic variants have improved the diagnostic yield, including a recent study on TSC1/TSC2 [ 74 , 75 , 76 ]. Most deep intronic variants will require functional studies for their pathogenicity to be evaluated as per guidelines from the American College of Medical Genetics and Genomics (ACMG) and Association for Molecular Pathology (AMP) [ 71 , 77 , 78 ].…”
Section: Overview Of Genetics Of Tscmentioning
confidence: 99%
“…In neurological tissue, intronic pathogenic variants that cause aberrant exonization have been associated with milder phenotypes (sometimes with only one clinical feature present in a systemic disease) hypothesized to be explained by significantly abrogated, but not eliminated, canonical transcript expression [ 76 , 102 , 103 ]. In a recent cohort study reevaluating NMI TSC patients with a definite or possible clinical TSC diagnosis, 19/155 individuals presented with deep intronic variants; of these intronic carriers, several of them did not have a definite clinical diagnosis nor did they display as many systemic features as did the rest of the cohort [ 74 ].…”
Section: Summary Of Genotype–phenotype Correlations For Tscmentioning
confidence: 99%